THE EFFECT OF RETURN ON ASSETS, INVENTORY TURNOVER AND DEBT TO EQUITY RATIO ON STOCK PRICES WITH EARNINGS PER SHAREAS MODERATING VARIABLES IN COMPANIES TECHNOLOGIES LISTED ON THE INDONESIA STOCK EXCHANGE - Herlambang, Guntur; Satriawan, Bambang; Robin, Robin; Wibisono, Chablullah; Khaddafi, Muammar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to examine the effect of Return on Assets, Inventory Turnover, Debt to Equity Ratio, on stock prices with Earning Per Share as a moderating variable in technology sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. This study uses secondary data. This study uses a purposive sampling technique with a sample of 8. The data analysis technique used is moderated regression analysis (MRA) with the help of Eviews 10 software. Based on the test results, it is known that the ROA variable has a negative and insignificant effect on stock prices, with the significance value is 0.953 where the ROA significance value is greater than 0.05, thus the first hypothesis (H1) is not accepted. The next result is that ITO has a negative and insignificant effect on stock prices, with a significance value of 0.542 where the ITO significance value is greater than 0.05, thus the second hypothesis (H2) is not accepted. Then DER has a negative and insignificant effect on stock prices, with a significance value of 0.522 where the significance value of DER is greater than 0.05, thus the third hypothesis (H3) is not accepted. Furthermore, EPS has a positive and significant effect on stock prices, with a significance value of 0.000 where the EPS significance value is less than 0.05, thus the fourth hypothesis (H4) is accepted. The probability value of EPS moderation on ROA is 0.000 where the value is less than 0.05. This means that EPS moderates the effect of ROA on stock prices, this means (H5) is accepted, the probability value of EPS moderation against ITO is 0.001 where the value is less than 0.05. This means that EPS moderates the effect of ITO on stock prices, this means that (H6) is accepted. The probability value of EPS moderation on DER is 0.014 where the value is smaller than 0.05. This means that EPS moderates the effect of DER on stock prices. This means that (H7) is accepted.